Life in the White House : a social history of the first family and the president's house - Watson, Robert P., 1962- (State University of New York Press, 2004)
"This perspective on the White House, one of the most readily identifiable structures in world, brings together the views of librarians, journalists, political advisers, attorneys, researchers, and professors. Filled with anecdotes, little-known facts, and scholarly analysis, the book shows how "The People's House" has been shaped and molded both architecturally and philosophically by the different administrations over the past 200 years." "Life in the White House looks at the social history of the first family, the creation of the president's home, and efforts by first families to carve out a space for the important business of family, while preserving the history of their famous residence. This public museum and private residence, which began as the result of a $500 Jefferson-era architectural design contest, now symbolizes one of the world's great superpowers."--Jacket